Mungkinkah Nilai Perusahaan Dapat Menurun jika Melakukan Penghindaran Pajak dengan Melihat Kepemilikan Institusional Perusahaan - Supriadi, Adi (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The purpose of this study is to examine how much impact the tax avoidance complex and institutional ownership can have on the value of companies listed on the Indonesian stock exchange. The object of this study is a professional company listed on the stock exchange, data taken from annual reports and websites of sample companies. The analysis tool uses eviews 9, research data for the period 2019 to 2023. The results of this study are around 3.4% of the company's value is influenced by tax avoidance and institutional ownership, but the rest is still influenced by other factors, so that further researchers can add tax planning variables with various proxies to further increase the company's value. Recommendations for companies not to do a lot of tax avoidance that is not in accordance with regulations because it will reduce the company's value. It can be seen from the negative influence between company value and tax avoidance.